2022
DOI: 10.3390/ijerph19063282
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mindfulness Meditation on Doctors’ Mindfulness, Patient Safety Culture, Patient Safety Competency and Adverse Event

Abstract: Objective: This study investigated the effects of mindfulness meditation on doctors’ mindfulness, patient safety culture, patient safety competency, and adverse events. Methods: We recruited 91 doctors from a hospital in China and randomized them to mindfulness meditation group (n = 46) and a waiting control group (n = 45). The mindfulness meditation group underwent an 8-week mindfulness meditation intervention, while the control group underwent no intervention. We measured four main variables (mindfulness, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 79 publications
0
20
0
Order By: Relevance
“…Research on mindfulness is generally divided into trait mindfulness and state mindfulness ( Randal et al, 2015 ). State mindfulness can be changed due to internal and external environmental stimuli and lasts for a short time ( Liu et al, 2022a ), and this state is not fixed ( Said and Tanova, 2021 ). Trait mindfulness is a tendency to remain stable over time, that is, individuals actively and consciously pay attention to the surrounding environment and remember relevant useful information, so that the mind can focus more on the objects related to the goal and be more determined ( Wang X. et al, 2021 ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Research on mindfulness is generally divided into trait mindfulness and state mindfulness ( Randal et al, 2015 ). State mindfulness can be changed due to internal and external environmental stimuli and lasts for a short time ( Liu et al, 2022a ), and this state is not fixed ( Said and Tanova, 2021 ). Trait mindfulness is a tendency to remain stable over time, that is, individuals actively and consciously pay attention to the surrounding environment and remember relevant useful information, so that the mind can focus more on the objects related to the goal and be more determined ( Wang X. et al, 2021 ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…The literature on adverse events (AEs) in mindfulness-based treatments is sparse and in its infancy [ 48 , 49 , 50 ]. A recent review by Binda and colleagues stresses AEs for meditation practice, including anxiety and pain, and more severe events such as psychosis or mania.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few years, the benefits of mindfulness have received more attention in research. It has been found that mindfulness can bring benefits to individuals such as: maintaining mental health (Brown and Ryan, 2003 ), increasing subjective well-being (Liu et al, 2020a ), enhancing intensity of attention and mental lucidity (Hanley and Garland, 2017 ), increasing productivity (Liu et al, 2020b ), reducing stress (Huberty et al, 2019 ) and depression (Jones et al, 2022 ), improving patient safety competence levels (Liu et al, 2022a ), and becoming a viable treatment option for anxiety disorders (Boettcher et al, 2014 ). Aside from these advantages, mindfulness began to play a greater role with high social value as scholars began to explore its application in other fields, and it has become a subject of interdisciplinary research (e.g., sociology, family studies, education, anthropology, philosophy, economics, and organizational science).…”
Section: Theoretical Frameworkmentioning
confidence: 99%